2020
DOI: 10.1590/0104-1428.09319
|View full text |Cite
|
Sign up to set email alerts
|

Development of active PHB/PEG antimicrobial films incorporating clove essential oil

Abstract: In this work were developed and evaluated new antimicrobial films of polyhydroxybutyrate (PHB) additivated with polyethyleneglycol (PEG) and clove essential oil (CEO). The PHB/PEG/CEO films were prepared using the solution casting technique. The CEO concentrations varied between 0.0 and 15% (w/w), related to the total mass (1.4 g), without considering the solvent used. The CG-MS analysis showed that the major component of the CEO was eugenol (72.96%). The antimicrobial activity from the CEO was evaluated again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Silva et al (2020), while studying antimicrobial films made from PHB/PEG incorporated with clove essential oil, obtained, by GC–MS, an eugenol composition of 73%, which is the same as found in this study. The authors confirmed, by the elevated eugenol concentrations, the oil’s potentiality for being used as an antimicrobial agent against a number of pathogens.…”
Section: Resultssupporting
confidence: 81%
“…Silva et al (2020), while studying antimicrobial films made from PHB/PEG incorporated with clove essential oil, obtained, by GC–MS, an eugenol composition of 73%, which is the same as found in this study. The authors confirmed, by the elevated eugenol concentrations, the oil’s potentiality for being used as an antimicrobial agent against a number of pathogens.…”
Section: Resultssupporting
confidence: 81%
“…In research, PHA-based film incorporated with clove essential oil was prepared for active food packaging purposes. No microbial growth was reported on the film surface [139]. Migration is a key issue in food packaging since monomers or additives employed in PHA preparation might conceivably migrate into the food matrix.…”
Section: Polyhydroxyalkanoates (Phas)mentioning
confidence: 99%
“…Clove (Eugenia caryophyllata) EO has the volatile aromatic oil eugenol as its main component, which has antibacterial, antifungal, antioxidant, insecticidal, and antiviral properties (Silva, I. D. L. et al 2020. The presence of eugenol also increases the anti-inflammatory and the antioxidant properties of films and coating for, e.g., apples, strawberries, and ground beef (Santana et al 2021).…”
Section: Films Containing Essential Oilsmentioning
confidence: 99%
“…Clove EO was incorporated with polyethylene glycol to polyhydroxybutyrate films, and the addition of 15% w/w changed the chemical structure of the material, resulting in less energy during film processing and more flexible films (Silva, I. D. L. et al 2020). Clove EO was utilized in the formulation of cassava starch-based films in combination with montmorillonite clay and glycerol.…”
Section: Films Containing Essential Oilsmentioning
confidence: 99%